OPPORTUNITY LOSS ANALYSIS OF DISCHARGE AGAINST MEDICAL ADVICE (DAMA) AT INPATIENT UNIT OF TYPE A HOSPITAL IN SURABAYA - Bilqis, Nabilah; Prakoso, Seta (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Patients who Discharge Against Medical Advice (DAMA) will experience the opportunity loss. DAMA will result in opportunity loss for patients to get treatment and cure their illness. For hospitals, DAMA patients will cause the opportunity loss for hospitals to provide services to patients. Aim: The purpose of this research was to analyze the opportunity loss as the result of DAMA patient. Methods: The method used in this research was a descriptive research. The samples were chosen from the total sample of inpatient population who did DAMA as many as 77 medical records. The inclusive samples were doctors who were responsible for other doctors and dentists as well as inpatient medical records. Meanwhile, the exclusive samples were doctors who are not responsible for other doctors and dentists as well as inpatient medical records. Data analysis used Microsoft Excel to see the total and percentage of DAMA patients. Results: The number of DAMA patients was 77 patients. The highest number of DAMA patients was those in grade 3 as many as 25%. It happened because the grade 3 was cheaper than others. As many as 65% of DAMA patients paid hospital fees using general payments. Patients felt free to discharge themselves from the hospitals because they funded on their own. The majority of DAMA patients were type 2 DM patients amounted to 12% because they assumed they could carry out self-care at home. Conclusions: DAMA patients caused opportunity loss and no Social Security Agency for Health (BPJS Kesehatan) guarantees. Therefore, the hospital has to form a policy to prevent patients from DAMA, notify and ask patients' reasons of doing DAMA, so the hospital can use these as information for hospital service evaluation. Keywords: Opportunity loss, DAMA, Hospital.